(3GdfXQjI GdGbJUGOjI GdcdjIs - (3YHO GdQMeGf GMeO(B, (3jSQjs; (3eMH Rcj GjeGf(B, s ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2007)
(3jYQV gPG GdcJGH eGjdj (B: (3ebOeGJ GSGSjI (B/(3GdfehPL GdcdGSjcj (B/(3GdfehPL GdcfRj (B/(3GKQ GdfbhO Ydi GdONd Gdbhej GdMbjbj (B/(3JMOjO JhGRf GdONd Gdbhej eY GdeSJhi GdYGe ddGSYGQ (B/(3GdJVNe (B/(3GdHWGdI (B/(3GdGWGQ GdYGe dJMdjd Gdefh GdGbJUGOj (B/(3GdJfejI GdGbJUGOjIs
(3HjHdjhZQGajG U(B.319s
Keywords: (3GbJUGO cdjs; (3GdHWGdIs; (3GdONd Gdbhejs; (3GdfbhOs